Pengaruh Konseling Kelompok Pendekatan Behavioral Terhadap Kedisiplinan Siswa Kelas VIII SMP Negeri 23 Medan - Aini Kurniawati Suranta; Khairani Ulfa Syaimi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The discipline of students at SMP Negeri 23 Medan looks very lacking and also in that school where the bk teacher overcomes 1000 students while the bk teacher is only 1 person, so that the bk teacher is overwhelmed. This study aims to determine the effect of behavioral approach group counseling on student discipline. The method in this research is quantitative research One Group Pretest-Posttest research design. The population in this study were male students of class VIII D SMP Negeri 23 Medan class year 2025. The sampling technique used was purposive sampling. The male students sampled in this study were 10 people with student discipline scores in the low category. The instrument used in determining the sample of this study was a student learning discipline instrument with four choices in a Likert scale model consisting of 31 valid items with reliability using Cronbach's alpha of 0.825. Statistical data analysis techniques were carried out using descriptive statistics using empirical means to see the average pretest and posttest scores before treatment and after treatment. This study used the Paired Sample T-Test. Based on the results of the study, it is known from the results of the sig value. (2-tailed) 0.001 <0.05 means Ha is accepted and Ho is rejected. This shows that there is an effect of behavioral approach group counseling on the discipline of students in class VIII SMP Negeri 23 Medan.